Let’s Talk about Sex: Teaching Adolescents with Intellectual Disability about Sexuality Education - Anis Raihan Dzeidee Schaff; Fitri Suraya Mohamad (Indonesian Journal of Cultural and Community Development, 2019)
This qualitative case study explores the experiences of teachers who are responsible for teaching adolescents with intellectual disability about sexuality education at a secondary school in a special education programme in semi-rural Sarawak. The study investigates the teaching approaches to teach cognitive and social-behavioural aspects of sexuality education. It also documents challenges in teaching adolescents with intellectual disability about sexuality education. Findings revealed that cognitively, the adolescents’ comprehension and memory are greatly aided by the use of concrete materials, modelling strategy, and constant repetition; attention and focus in class are obtained by the use of multimedia and storytelling approach; and interestingly, the understanding about sexuality is affected by the language used in content delivery and classroom dialogue. In the social-behavioural aspect, the findings revealed the importance of teachers and students’ comfort when talking about sexuality, mixed gender classes, peer guidance, and the adolescents’ intrapersonal intelligence. All these aspects are key in ensuring that the adolescents are able to reach an understanding and acceptance towards learning about sexuality education. The study also discovered that limitation of teaching materials, the adolescents’ unsupervised usage of the technology, and the sensitivity of sexuality education within the local home setting are among the main challenges faced by the teachers in teaching about sexuality education. The study also uncovered how the adolescents’ limited mental capabilities particularly in the social-behavioural domain has resulted in the adolescents displaying tendencies toward sexually risky behaviours which in turn, exposed them to sexually risky situations.